Institutions in System Implementation Waste Water Management Domestic Centralized (SPALD-T) in Pekayon Village Subdistrict Sukadiri Tangerang Regency - Setiawati, Rahmalia; Cadith, Juliannes (Jurnal Multidisiplin Indonesia, 2024)
This study aims to determine the role of institutions in the implementation of the Centralized Domestic Wastewater Management System (SPALD-T) in Pekayon Village, Sukadiri Subdistrict, Tangerang Regency. The research method used is qualitative, with a descriptive approach. The data processing techniques used in this research are observation, interviews, and documentation. The data analysis used in this research is interactive analysis, according to Miles and Huberman. In this study, the data credibility test was used to test the validity of the data. The data credibility test was carried out by triangulation. The results of this study indicate that the institutional effectiveness of regional apparatus organizations in Tangerang Regency is not yet effective. In terms of leadership, the Tangerang Regency Government has issued Tangerang Regent Regulation No. 80/2017 on Domestic Wastewater Management as a guideline for the implementation of SPALD-T. In terms of doctrine, the Tangerang District government's efforts to indoctrinate the community to actively participate in the implementation of SPALD-T in Pekayon Village are not optimal. Next, the program aspect has led to the fulfillment of community rights, which is also in accordance with the design that has been made, but many targets have not been achieved. Furthermore, the overall resources aspect is still lacking and cannot be utilized optimally. Then, in terms of internal structure, the Tangerang District Government's institutional strengthening is lacking because there is no organizational structure for the DPOs involved in SPALD-T implementation, and communication between DPOs is not good.